Performance of Acid Leached Rice Husk Ash (ARHA) in Mortar - Seng Wong, Yong (International Journal of Integrated Engineering, 2019)
RHA is one the most available agricultural wastes in rice producing countries. Roughly of 20% of the total amount of paddy is husk which giving an annual total production of 120 Mtons which causes disposal problem due to low commercial interest and uses. The presence of metal impurities (Na2O and K2O) in non-treated RHA that incorporating in concrete can trigger alkali reaction in harden concrete. In order to overcome the issue, hydrochloric acid as the leaching agent for acid leaching treatment on RHA effectively removed metallic impurities from the RHA. In this study, ARHA was prepared by acid leaching treatment in order that the end product conformed to the engineering standards in terms of chemical and morphological properties. There are total of 3 proposed acid leaching parameters on RHA (1 M, 0.1 M and 0.01 M HCl leaching treatment with the duration of 2 days) prior to combustion at 800oC for 2 hours. The chemical properties and morphology study of the ARHA would be firstly characterized base on the x-ray fluorescent (XRF), x-ray diffraction (XRD), particle size analyzer, loss on ignition (LOI) and BET analyzer. 0.1 M of HCl leaching treatment RHA (ARHA2) prior to combustion at 800oC for 2 hours effectively removed impurities and produced > 90 % of pure amorphous silica with high surface area and pore volume. Hence, the effects of incorporating ARHA2 as partial replacement (2.5 %, 5 %, 7.5 %, and 10 %) of cement were investigated. The compressive strength, ultrasonic pulse velocity (UPV), porosity, gas permeability and the water absorption of ARHA mortar were determined to identify the characteristics of AHRA mortar. The results show that the replacement 10 % of ARHA into the mortar gave a positive result, it improved 29% of compressive strength compared to the control mix. In term of durability properties, there was approximate 2.2 % reduction in the total porosity as the replacement level of ARHA2 increased from 0 % to 10 % of total binder in the mortar.